The Raising of Lazarus: Caravaggio and John 11 - Oates, Amy (Interpretation, 2007)
Combining art historical and biblical scholarship, this article examines John 11 to offer textual reasons for the unique motifs and composition in Caravaggio's Raising of Lazarus (1608–09) and to provide greater insight into the painting and its source.